Bariatric surgery affects obesity-related protein requirements. (December 2020) - Guillet, C.; Masgrau, A.; Mishellany-Dutour, A.; Blot, A.; Caille, A.; Lyon, N.; Pereira, B.; Slim, K.; Robert, M.; Disse, E.; Feugier, N.; Le Ruyet, P.; et al.
Summary: Context: Following bariatric surgery, protein deficiency intakes are reported in morbidly obese patients, whereas post-bariatric protein requirements are not specifically defined with validated method in this population. Objective: To assess average protein requirement (APR) in obese subjects, before, 3 months and 12 months after bariatric surgery using the validated method of nitrogen balance. Design and setting: Prospective longitudinal study conducted in 21 morbidly obese patients (BMI 43.9 ± 1.4 kg/m 2 ) before (M0), 3 months (M3) and 12 months (M12) after sleeve gastrectomy or Roux-en-Y gastric by-pass. An additional larger cross-sectional study was performed to validate APR before surgery in non-operated matched obese patients (n = 106). APR was evaluated at M0, M3, M12 by measuring 3 days dietary intakes together with losses of nitrogen in urine and stools. Main outcome measure: APR was defined as the mean value of protein intake required to achieve balance nitrogen equilibrium. Results: Before surgery, APR in morbidly obese patients was 0.76 [95%CI, 0.66–0.92] g/kg Body Weight (BW)/d in the experimental group, and 0.74 [0.70–0.80] g/kg BW/d in the validation group. APR was 0.62 [0.51–0.75] g/kg/d at M3 and 0.87 [0.75–0.98] g/kg/d at M12, with no difference between surgical procedures. Spontaneous protein intakes were respectively 0.80 ± 0.05, 0.43 ± 0.03 and 0.71 ± 0.04 g/kg BW/d respectively at M0, M3 and M12. Conclusion: This study demonstrates a temporal change in protein requirement after bariatric surgery whatever the type of surgery. Spontaneous protein intakes following bariatric surgery does not cover protein requirements for most patients, suggesting that specific dietary protein recommandations have to be adapted in obese patients with bariatric surgery. TRIAL REGISTRATION: Clinicaltrials.gov Identifier: NCT01249326.